An Implicit Mariology: A Study of the Incarnation, the Economy of Salvation, and Genealogical Language in the Pauline Epistles - QIAN, Yiting (Journal of Research for Christianity in China (JRCC), 2025)
Starting from Paul’s expressions such as “born of a woman” and “descended from David according to the flesh,” this study adopts a methodological approach that privileges theological interpretation while integrating textual exegesis and interdisciplinary insights from historical-critical studies, spiritual theology, and liturgical theology. Its purpose is to clarify the intrinsic relationship between Mary’s relation to the Incarnation and the twofold economy of salvation (Law/Spirit) as reflected in Paul’s letters. Although Paul does not elaborate extensively on Mary, in Galatians 4:4 he emphasizes that Christ was “born of a woman,” thereby affirming Mary’s pivotal role in the divine plan of salvation. Through faith and obedience, she became the gateway of God’s salvific economy and the channel of divine grace; her free assent allowed the Word of God to assume human nature and inaugurated a new history of cooperation between God and humanity. Mary is thus not only the mother of Jesus but also the spiritual mother of all believers. While Paul’s theology does not explicitly develop a Marian doctrine, it provides the foundational framework upon which later Church tradition deepened and confirmed Mary’s place within the mystery of salvation.